Pengaruh Desain Pekerjaan Dan Budaya Organisasi Terhadap Kinerja Sumber Daya Manusia Yang Dimediasi Oleh Motivasi Kerja - Moelki Kaswary; Jeliteng Pribadi (Syiah Kuala University Press, 2023)
This study aims to determine the influence of job design and organizational culture on human resource performance mediated by work motivation in the Forest Security Unit of the KPH (II) of the Aceh Province Environment and Forestry Service. This study uses primary data obtained by directly distributing questionnaires as a data collection instrument. The population in this study were Pamhut members in the KPH (II) working area, totaling 283 members and the sampling technique used probability sampling using the Slovin formula to determine the number of samples taken in the study, and the sample results totaled 166 members. The data analysis method used is the Statistical Package for the Social Sciences (SPSS) as a tool to determine the effect between variables and use the Sobel test to determine the effect of intervening variables. Based on the results of the study, it was found that job design, organizational culture and work motivation had a positive and significant effect on HR performance. The results of the study also found that work motivation mediaties job design on HR performance in full mediation where the positive effect is not significant. Meanwhile, work motivation mediates organizational culture on HR performance by means of partial mediation where the effect is positive and significant.Keyword: Job design, organizational culture, human resource performance, work motivation, statistical package for the social sciences, sobel test